Advances in Targeting HER3 as an Anticancer Therapy. (7th November 2012) - Jiang, Ning; Saba, Nabil F.; Chen, Zhuo Georgia
Abstract : HER3 (ErbB3) is a unique member of the human epidermal growth factor receptor (EGFR) family (ErbB family). It functions only through dimerization with other members of the ErbB family and modulates activity and sensitivity to targeted cancer therapies. This paper briefly describes the mechanism of HER3 in signal transduction and its potential role in acquired resistance to EGFR- and HER2-targeted therapies. We also consider recent developments in HER3-targeting therapeutics and their combination with inhibitors of other ErbB members in clinical applications.